2015
DOI: 10.1097/md.0000000000000854
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Focused Ultrasound Combined With Suction Curettage for the Treatment of Cesarean Scar Pregnancy

Abstract: The aim of this study was to retrospectively evaluate the safety and feasibility of high-intensity focused ultrasound (HIFU) treatment combined with suction curettage under hysteroscopic guidance for cesarean scar pregnancy (CSP).Fifty-three patients with definite CSP were treated with HIFU followed by suction curettage under hysteroscopic guidance. All the patients received 1 session of HIFU ablation under conscious sedation. Suction curettage under hysteroscopic guidance was performed at an average of 2.9 (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 23 publications
3
65
0
Order By: Relevance
“…The aim of the operation was to remove the non-implanted part of the placenta; the deeply implanted part of the placenta was left in situ, to be absorbed slowly after the HIFU ablation. The average depth of the uterus was 10.36 AE 2.14 cm (range [8][9][10][11][12][13][14][15]. The median volume of any intraoperative blood loss was 20 ml (range 5-400); no blood transfusions were given.…”
Section: Hysteroscopic Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the operation was to remove the non-implanted part of the placenta; the deeply implanted part of the placenta was left in situ, to be absorbed slowly after the HIFU ablation. The average depth of the uterus was 10.36 AE 2.14 cm (range [8][9][10][11][12][13][14][15]. The median volume of any intraoperative blood loss was 20 ml (range 5-400); no blood transfusions were given.…”
Section: Hysteroscopic Operationmentioning
confidence: 99%
“…[9][10][11][12] Some reports on the treatment of PA by HIFU have been published recently, but the risk of haemorrhage and infection when using HIFU alone, is still high. In this study, we utilised USgHIFU combined with curettage guided by hysteroscopy to treat PA patients so that the chance of unexpected haemorrhage and infection from HIFU could be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Intraarterial MTX + UAE+ combined laparoscopy and hysteroscopy 25 patients, 100% success rate. Blood loss less than 200ml [50].…”
Section: Uae+ Hysteroscopic Surgerymentioning
confidence: 99%
“…UAE combined with local MTX or systemic MTX UAE combined with local MTX infusion has been used extensively in recent years, and it has been suggested that the effects of MTX are synergistic to UAE [50,51].…”
Section: Uae+ Hysteroscopic Surgerymentioning
confidence: 99%
See 1 more Smart Citation